2016
DOI: 10.1080/14737167.2016.1178066
|View full text |Cite
|
Sign up to set email alerts
|

An innovative outcome-based care and procurement model of hemophilia management

Abstract: Hemophilia is a rare bleeding disorder associated with spontaneous and post-traumatic bleeding. Each hemophilia patient requires a personalized approach to episodic or prophylactic treatment, but selfmanagement can be challenging for patients, and avoidable bleeding may occur. Patient-tailored care may provide more effective prevention of bleeding, which in turn, may decrease the likelihood of arthropathy and associated chronic pain, missed time from school or work, and progressive loss of mobility. A strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…For example, DMR may require more physician time; workloads, compensation, and time constraints issues should be considered . Likewise, despite some claims, chronic care management is often complex and incompletely understood; therefore, innovative therapies may require more experience and education, consistent with adaptive health practices . The role of trust should be better understood since its presence is thought to be essential to SDM .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, DMR may require more physician time; workloads, compensation, and time constraints issues should be considered . Likewise, despite some claims, chronic care management is often complex and incompletely understood; therefore, innovative therapies may require more experience and education, consistent with adaptive health practices . The role of trust should be better understood since its presence is thought to be essential to SDM .…”
Section: Discussionmentioning
confidence: 99%
“…The need for additional research and the lack of an integrated SDM theory are an identified gap in the literature and if developed will contribute to enhancing the use and impact of SDM in medical decision making . Recently proposed SDM models could benefit from an understanding of these factors …”
Section: Introductionmentioning
confidence: 99%
“…Recently published haemophilia decision‐making models of care promote ‘shared’, ‘deliberative’ or ‘tailored’ techniques to optimize treatment . These models reflect a shift from a paternalistic model of medicine to a process whereby healthcare providers and their patients make treatment decisions jointly.…”
Section: Introductionmentioning
confidence: 99%
“…Hemophilia care is changing. The importance of individualizing care in improving long‐term outcomes and quality of life, and reducing direct and indirect costs of treatment, is increasingly recognized . At the same time, patient expectations have been transformed, both in the management of the disease and the desire for treatment to be compatible with their lifestyle choices.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of individualizing care in improving long-term outcomes and quality of life, and reducing direct and indirect costs of treatment, is increasingly recognized. 1 At the same time, patient expectations have been transformed, both in the management of the disease and the desire for treatment to be compatible with their lifestyle choices. Prophylaxis is the standard of care for people with hemophilia (PWH), 2 but there is now greater understanding that rigid prophylactic regimens do not take into account an individual's bleeding propensity, existing burden of joint damage, or pharmacokinetic (PK) response to the FVIII replacement used, and beyond the clinical aspects, their personal expectations and lifestyle requirements.…”
Section: Introductionmentioning
confidence: 99%